2015
DOI: 10.1016/j.bbi.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphology links systemic inflammation to cognitive function in midlife adults

Abstract: Background Inflammation is linked to cognitive decline in midlife, but the neural basis for this link is unclear. One possibility is that inflammation associates with adverse changes in brain morphology, which accelerates cognitive aging and later dementia risk. Clear evidence is lacking, however, regarding whether inflammation relates to cognition in midlife via changes in brain morphology. Accordingly, the current study examines whether associations of inflammation with cognitive function are mediated by var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
204
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 107 publications
19
204
4
5
Order By: Relevance
“…Once a robust link between a biometric risk factor, such as body mass, and an outcome of clinical interest is established, it essential to test the more proximal potential biological mechanisms that might help explain this association using mediation models that integrate the relevant biological intermediary into the pathways from risk factor to outcome (Miller et al, 2009). Our measure of circulating inflammation, CRP (a measure of systemic inflammation in the periphery), evidenced a significant indirect effect that accounted for the association between body mass and cognition; circulating levels of systemic inflammation are associated neuro-inflammation (Marsland et al, 2015, Perry, 2004and Perry, 2010). Although we were unable to include measures of neuro-inflammation in our current study, our results match well with neurodegenerative models of cognitive decline and suggest that inflammation is one biologically plausible mechanism through which body mass might affect cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once a robust link between a biometric risk factor, such as body mass, and an outcome of clinical interest is established, it essential to test the more proximal potential biological mechanisms that might help explain this association using mediation models that integrate the relevant biological intermediary into the pathways from risk factor to outcome (Miller et al, 2009). Our measure of circulating inflammation, CRP (a measure of systemic inflammation in the periphery), evidenced a significant indirect effect that accounted for the association between body mass and cognition; circulating levels of systemic inflammation are associated neuro-inflammation (Marsland et al, 2015, Perry, 2004and Perry, 2010). Although we were unable to include measures of neuro-inflammation in our current study, our results match well with neurodegenerative models of cognitive decline and suggest that inflammation is one biologically plausible mechanism through which body mass might affect cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation in the periphery is tied to neuro-inflammation in neurodegenerative disorders (Perry, 2004), as well as in aging populations more generally (Perry, 2010). For example, IL-6 and C-reactive protein (CRP) assessed in the periphery are associated with changes in brain morphology and cognitive decline in midlife (Marsland et al, 2015). As a result, individual differences in systemic inflammation may explain a portion of the variability in cognitive decline among aging adults.…”
Section: Inflammation and Cognitive Declinementioning
confidence: 99%
“…Only three studies (32-34) investigated white matter microstructure and showed that systemic inflammation was associated with reduced fractional anisotropy (FA), an indicator of white matter integrity. CRP or IL6 was associated with reduced total brain volume (TBV)(35), total gray matter volume (TGMV)(36-38), total white matter volume (TWMV)(37), and hippocampal volume(36, 37, 39). However, CRP and IL6 were not associated with brain volumes in other studies (32, 33, 40-42).…”
Section: Introductionmentioning
confidence: 99%
“…However, CRP and IL6 were not associated with brain volumes in other studies (32, 33, 40-42). Only two studies examined whether inflammatory biomarkers were associated with cortical thickness (CT) and they found inconsistent results(37, 43). In one study of elderly adults, higher IL-6 was associated with accelerated annual rates of cortical thinning in the inferior temporal poles bilaterally(43), while another study found no cross-sectional associations of IL6 or CRP with CT in adults aged 30–54 years(37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation